NILAI-NILAI NASIONALISME DALAM NOVEL ANAK SEMUA BANGSA KARYA PRAMOEDYA ANANTA TOER (KAJIAN ANALISIS ISI) - Sumiharti Sumiharti; Dodi Alpayet (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
This research aims to describe the value of nationalism related to willingly sacrifice for the nation and state which includes the value of being willing to sacrifice time, energy and thoughts for the progress of the nation and state, the value of being ready to defend the nation and state from various threats, the value of actively participating in the development of society, nation and state, the value of being willing to help fellow citizens who have difficulties in the novel Anak Semua Bangsa by Pramoedya Ananta Toer. This research includes qualitative descriptive types. Qualitative descriptive research is research that describes an event with words or a picture of the state of the subject who is in a particular environment and situation. From the results of this study, it can be described that the value of nationalism is related to willingly sacrificing for the nation and state; The value of being willing to sacrifice time and thoughts for the progress of the nation and state, the value of being ready to defend the nation and state from various threats, the value of actively participating in the development of the nation and state, fond of helping fellow citizens who experience difficulties in the novel Anak Semua Bangsa  by Pramodya Ananta Toer. The value of nationalism related to willingly sacrifice for the nation and the most dominant country in the novel Anak Semua Bangsa by Pramoedya Ananta Toer, namely the value of actively participating in the development of society, nation and state as many as 23 quotations, while the value of the least value is willing to sacrifice time, energy and thoughts for the progress of the nation and state as many as 12 quotations.